Transcranial Direct Current Stimulation and Behavioral Models of Smoking Addiction - Fraser, Paige; Rosen, Allyson (Frontiers in Psychiatry, 2012)
While few studies have applied transcranial direct current stimulation (tDCS) to smoking addiction, existing work suggests that the intervention holds promise for altering the complex system by which environmental cues interact with cravings to drive behavior. Imaging and repetitive transcranial magnetic stimulation (rTMS) studies suggest that increased dorsolateral prefrontal cortex (DLPFC) activation and integrity may be associated with increased resistance to smoking cues. Anodal tDCS of the DLPFC, believed to boost activation, reduces cravings in response to these cues. The finding that noninvasive stimulation modifies cue induced cravings has profound implications for understanding the processes underlying addiction and relapse. TDCS can also be applied to probe mechanisms underlying and supporting nicotine addiction, as was done in a pharmacologic study that applied nicotine, tDCS, and TMS paired associative stimulation to find that stopping nicotine after chronic use induces a reduction in plasticity, causing difficulty in breaking free from association between cues and cravings. This mini-review will place studies that apply tDCS to smokers in the context of research involving the neural substrates of nicotine addiction.